Saghar Siddiqui and Abdul Hameed Baba’s Philosophy of Contentment - Ali, Anwar; Seemab, Sher Zaman; Uddin, Shahab (sourcecoder, 2023)
We find good examples regarding contentment in the words of Saghar Siddiqui and Abdul Hameed Baba. Both poets are recognized writers and poets of their time. Abdul Hameed Baba is one of the famous Pashto poets whose words are embellished with religious traditions. On the other hand, Saghar Siddiqui was famous for his patience. This is the reason that both are remembered in history in high repute. In their poetry, the veil has been removed from the facts close to life. We can see the suffering for human beings in their poetry. It can be inferred from their poetry that both were eminent scholars. Both observed the society closely, examined, tested and drew conclusions. In this article, the point of view of both is being presented regarding contentment.